HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI DASAR DENGAN KECEMASAN DI POSYANDU KELURAHAN PASAR BARU KECAMATAN SEI TUALANG RASO TAHUN 2019 - Sumiatik; Lolita Nugraeny; Dharmawati (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2020)
Immunization is a way to actively increase a person's immunity against an antigen, so that if one is exposed to a similar antigen, disease does not occur. Immunization is important to prevent dangerous diseases. The purpose of this study was to determine the relationship between mother's knowledge about basic immunization and anxiety at Posyandu, Pasar Baru Village, Sei Tualang Raso District in 2018. The research design used in this study is descriptive correlation which is a study of the relationship between two variables. all mothers who have toddlers in the Pasar Baru district, Kec. Sei Tualang Raso. With a population of 36 people. Data analysis using the C-Square test. Results of the research conducted on the majority of respondents with low knowledge as many as 15 people (42%). The frequency of basic immunization with anxiety was 21 people (58%). C-Square Test Results Show a (0.05) obtained X2 = 0.04 p (sig) 0.138 <0.05. Based on the results of this study, it can be concluded that there is a relationship between maternal knowledge about basic immunization with anxiety. So it is advisable for health workers to provide information to the public about basic immunization with anxiety levels.